Learning Culture, Empowerment, Cyber Skill Competence And Self-Engagement (International Journal of Scientific Research and Management (IJSRM), 2018)
This study aim at determining the effect of learning culture, empowerment, and cyber skill competence on the employee’s self-engagement. The research used quantitative approach with survey method and path analysis applied in testing hypothesis. The research was conducted at Directorate General of Defense Potential with a sample of 150 employees selected through simple random sampling. The research found: (1) there is positive direct effect of learning culture on self-engagement, (2) there is positive direct effect of empowerment on self-engagement, (3) there is positive direct effect of cyber skill competence on self-engagement, (4) there is positive direct effect of learning culture on cyber skill competence, (5) there is positive direct effect of empowerment on cyber skill competence, and (6) there is positive direct effect of learning culture on empowerment. The conclusion showed that learning culture, empowerment, and cyber skill competence are important determinants to increase the employee’s self-engagement at Directorate General of Defense Potential Ministry of Defense RI